2020
DOI: 10.1002/cyto.b.21940
|View full text |Cite
|
Sign up to set email alerts
|

Multicentric MFI30 study: Standardization of flow cytometry analysis of CD30 expression in non‐Hodgkin lymphoma

Abstract: CD30 transmembrane receptor, a member of the tumor necrosis factor receptor family, is expressed in different lymphomas. Brentuximab vedotin (BV), a CD30 monoclonal antibody (Ab)-drug conjugate, is effective in CD30-positive lymphomas.However, the response to BV is not always correlated to CD30 expression detected by immunohistochemistry (IHC). The objectives of this study were to standardize and evaluate CD30 intensity by flow cytometry (FCM) in non-Hodgkin's lymphomas.Twelve centers analyzed 161 cases on sta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 32 publications
1
7
0
Order By: Relevance
“…Since IHC preserves the tissue architecture, it is used for routine clinical practice in lymphoma diagnosis while FCM is restricted to NHL with peripheral blood or bone marrow involvement or in chronic lymphocytic leukemia 32 .Over the years, multiple analytical techniques have been developed for clinical diagnosis, classi cation and monitoring of hematopoietic disease. FCM is a sensitive, accurate and realtime detection that was widely used in the evaluation of hematopoietic diseases 33 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Since IHC preserves the tissue architecture, it is used for routine clinical practice in lymphoma diagnosis while FCM is restricted to NHL with peripheral blood or bone marrow involvement or in chronic lymphocytic leukemia 32 .Over the years, multiple analytical techniques have been developed for clinical diagnosis, classi cation and monitoring of hematopoietic disease. FCM is a sensitive, accurate and realtime detection that was widely used in the evaluation of hematopoietic diseases 33 .…”
Section: Discussionmentioning
confidence: 99%
“…FCM is a laser-based technology, which measures living cells immunophenotype based on Ag-Ab reaction without structural alteration. FCM has some advantages compared with IHC: (1) FCM provides faster and accurate quantitative results; (2) FCM evaluates millions of cells labeled with different markers simultaneously and can easily de ne clonal populations; (3) FCM directly examines living cells and immunophenotypes in physiological state 32,34 . What's more, CART immunotherapy is effective for CD19-dim B-cell ALL, according to research in vitro, CART was able to recognize and lyse cells with CD19 expression in very low levels 35 .…”
Section: Discussionmentioning
confidence: 99%
“…There are insufficient immuno-phenotypic guidelines for the investigation of certain lymphomas (Tsagarakis et al, 2022). Multicentric efforts have been made to standardize FC analysis of CD30 expression in non-Hodgkin lymphoma (Debliquis et al, 2021). There is also a report on using CD43 and CD200 surface expression they do improve accuracy of Bcell lymphoma immunophenotyping (Dronca et al, 2010).…”
mentioning
confidence: 99%
“…The submitting authors have hypothisized that the occurrence of BIA-ALCL in Brazil is underreported, and therefore it is important to focus on this subject to better investigate this disease. In this report, the authors concluded that the application of FC with a comprehensive antibody panel consisting of CD30 in conjunction with CD25 and HLA-DR can discriminate anaplastic cells of breast implantassociated anaplastic large cell lymphoma from lymphoid or neutrophilic reactive cells and should be considered in the initial evaluation of these lymphoma entities(De Azambuja et al, 2022;Debliquis et al, 2020;Wong-Arteta et al, 2020).CAR-T-cell therapy has been recently approved in United Statesand Europe for the treatment of several hematological malignancies, since it achieved impressive results in patients with relapsed/ refractory B-acute lymphocytic leukemia (B-ALL) and diffuse large B-cell lymphoma (DLBCL)(Johansson et al, 2021;Maryamchik et al, 2020;Sarikonda et al, 2020;Yu et al, 2022). However, an increasing body of evidence suggests that a sizeable proportion of patients treated with CAR-T cells do not experience a long-term response.…”
mentioning
confidence: 99%